2018
DOI: 10.1002/anie.201800973
|View full text |Cite
|
Sign up to set email alerts
|

Concerted Catalysis by Adjacent Palladium and Gold in Alloy Nanoparticles for the Versatile and Practical [2+2+2] Cycloaddition of Alkynes

Abstract: A Pd-Au alloy efficiently catalyzed the [2+2+2] cycloaddition of substituted alkynes. Whereas monometallic Pd and Au catalysts were totally ineffective, Pd-Au alloy nanoparticle catalysts with a low Pd/Au molar ratio showed high activity to give the corresponding polysubstituted arenes in high yields. A variety of substituted alkynes participated in various modes of cycloaddition under Pd-Au alloy catalysis. The Pd-Au alloy catalysts exhibited high air tolerance and reusability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Supported Pd–Au alloy catalysts were prepared by a colloid immobilization method. , PVA and NaBH 4 aqueous solution were used as protecting and reducing agents, respectively. More detailed descriptions of the preparation methods are in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…Supported Pd–Au alloy catalysts were prepared by a colloid immobilization method. , PVA and NaBH 4 aqueous solution were used as protecting and reducing agents, respectively. More detailed descriptions of the preparation methods are in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…In 2018, Shishido, Miura, and co-workers reported the [2+2+2] cycloaddition reaction of substituted alkynes over supported Pd-Au alloy catalysts prepared through a sol-immobilization method (Scheme 51). 113 The Pd/Au ratio was a crucial factor for the catalytic activity and the compatibility of this catalyst with open-air conditions. Notably, the 1Pd4Au/TiO 2 catalyst was highly air tolerant and allowed the [2+2+2] cross-cycloaddition of 1,6-diynes with alkynes on a wide substrate scope in 37-95% yield.…”
Section: Other Metal-catalyzed [2+2+2] Cycloadditionmentioning
confidence: 99%
“…As solid catalysts, synergistic effects ascribed to the concomitant presence of two metals within nanosized aggregates, nanoclusters or nanoparticles, have been shown to unlock favourable, in some instances unique, catalytic performances in a broad range of conversion processes. [7][8][9][10] Pioneering work in this area by Sinfelt et al in alkane dehydrogenation and hydrogenolysis reactions 11,12 was followed by a surge of studies which demonstrated the potential of bimetallic catalysts in a wide array of reactions, from oxidation, [13][14][15] to hydrogenation, [16][17][18][19][20] reforming, 21 biomass conversion, 5 C-C coupling, 22 or acetoxylation catalysis. 23 The distinctive catalytic properties of bimetallics compared to their monometallic counterparts has been associated to factors such as differences in lattice strain and surface topology, intermetallic charge transfer phenomena, or atomic-scale surface dilution phenomena of one metal within a matrix of second metal (also referred to as single-atom alloys).…”
Section: Introductionmentioning
confidence: 99%